Performance Evaluation Of Listed Commercial Banks In Botswana: The Camel Model - Sathyamoorthi, Chirayathmadhom Ramachandran; Mapharing, Mogotsinyana; Ndzinge, Shabane; Tobedza, Gobona; Wally-Dima, Lillian (Archives of Business Research, 2017)
The study evaluated the financial performance of three listed commercial banks in Botswana for the period 2011-2015 applying the CAMEL model. The study used the secondary data sourced from the annual reports of the listed banks. Results indicate that selected banks were highly leveraged and that their liquidity position was sound. The correlation analysis revealed that Earning per share had a significant positive correlation with liquidity ratio of total customer deposits to total assets and that leverage ratio was significantly negatively correlated to the ratio of equity capital to assets. Other CAMEL ratios were not significantly correlated to Earnings Per Share. The regression analysis showed that Capital adequacy, Asset quality, Earning ability and Managerial efficiency had no significant relationship with selected banks’ performance measured in terms of Earnings per share. On the other hand, the Liquidity position of these banks was found to be significantly related to the performance of selected banks at 5% significance level. The findings also indicated that, overall, the selected banks performed well during the study period in terms of most of the parameters of CAMEL model with adequate capital and assets when compared to benchmarks. The earning capacity of the selected banks was also on the increase. The findings of this study will be helpful to the management of selected banks in making appropriate managerial decisions.